Identifikasi Tantangan Sekolah dan Guru dalam Program Sekolah Menengah Kejuruan Pusat Keunggulan - Amir Fatah; Mausa Agrevinna; Rachel Arimbi; Fatimah Azzahra; Purwanto Purwanto (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
The suitability of the competence of Vocational High School graduates with the needs in the industry is absolutely necessary. The Center for Excellence Vocational School (SMK PK) program is a program that encourages a comprehensive and harmonious relationship between schools and industry. The SMK PK program covers the areas of curriculum, learning, increasing the number and role of instructors from industry, industrial practice, competency certification, technology updates, applied research, and the uptake of graduates by the world of work. The SMK PK program mentioned above is certainly a new challenge for both schools and teachers. The purpose of this community service is to identify the challenges faced by schools and teachers in the PK Vocational School Program. This is important to do because through this identification activity, community service activities will be carried out according to needs. The method used is in-depth interviews to obtain comprehensive information on the challenges faced by schools and teachers. The results obtained are that schools still face difficulties in establishing relationships with industry so that it has an impact on curriculum development, learning implementation, the presence of instructors from industry, and work internships. While the problem faced by teachers is understanding of the operational curriculum, limited information and training, many new terms are used in the curriculum. Therefore, facilitation of partnering with industry and training on teacher understanding of the curriculum need to be carried out.